Visual Representational Analysis of Meaning in Pond's Men and Garnier Men TV Commercials - Riza, Resty Septia; Hamzah, Hamzah (English Language and Literature, 2021)
AbstractThis research aims to examine the difference of meaning in visual analysis in Pond's Men and Garnier Men advertisements. The purpose of this research is to find the difference in meaning in the visual analysis of Kress and Leeuwen metafunction which included representational, interactional, and compositional. The data were analyzed using the theory of The grammar of visual design Kress and Leeuwen (1996). The data is the visual contained in the Pond's Men and Garnier Men advertisement videos. The method of this research uses descriptive qualitative research. The results showed that there were some differences in Pond's Men and Garnier Men advertisements in visuals which are narrative actional transactional and narrative reactional transactional in representation, social, detachment, viewer power, and representation in interactional, and foregrounding and backgrounding in compositional.